Analisis Normatif Tentang Baby Blues Syndrome Sebagai Faktor Pemicu Kekerasan Ibu Terhadap Anak Dalam Perspektif Hukum Pidana Dan Hak Anak - Wikantari, Ida Ayu Putu; Wulandari, Ni Gusti Agung Ayu Mas Tri (Consensus : Jurnal Ilmu Hukum, 2025)
The phenomenon of postpartum baby blues syndrome is often considered a psychological issue, but in reality it can have serious legal consequences, especially when it leads to violence against children and causes fatalities. This study aims to conduct a normative assessment of the relationship between baby blues syndrome and maternal violence against children, particularly from the perspective of criminal law and children's rights. The method used is normative legal research with a legislative, conceptual, and case study approach. The results of the study show that this syndrome is influenced by various factors that have the potential to encourage maternal violence against children. In criminal law, this psychological condition cannot be used as a reason to eliminate criminal responsibility, but it can be considered by the judge as a mitigating factor if it is proven that the perpetrator has a mental health disorder. Meanwhile, from the perspective of children's rights, all forms of violence are still considered serious violations that threaten children's rights to live, grow, and develop properly. Therefore, preventive measures are needed to reduce the number of mothers experiencing baby blues syndrome after childbirth while minimizing the risk of violence against children in Indonesia.